Rubella seroprevalence among unvaccinated Adolescent girls in chennai - RAMYAA RAJENDIRAN; SHANTHI RAMESH; JAGDEEP RAMESH (International Journal of Pharma and Bio Sciences, 2017)
Rubella infection occurring during early pregnancy results in Congenital Rubella Syndrome. To estimate the seroprevalence of rubella among adolescent girls attending a tertiary care hospital. 75 adolescent girls in the age group of 10- 19 years who had not received MMR vaccine were included in the study. Serum IgG antibody titre for rubella was estimated by the ELISA method. 78.7% of the adolescent girls were found to be rubella seropositive.The urban adolescent girls had a higher seropositivity of 85.2% as compared to rural adolescent girls (P value= 0.0004). The socioeconomic status was not significantly associated (P>0.5) with rubella seroprevalence. The study indicates that a substantial number of adolescents (21.3%) are seronegative and hence susceptible to rubella infection. Hence, India should focus on the addition of catch up vaccination for Rubella among adolescent girls in the National Immunization Schedule to prevent congenital rubella syndrome.